A new species of Peltephilidae (Mammalia: Xenarthra: Cingulata) from the late Miocene (Chasicoan SALMA) of Argentina - Gonzalez Ruiz, Laureano Raul (2012)
A new species of Peltephilidae (Mammalia, Xenarthra, Cingulata) (early Eocene–late Miocene) is described here. The new taxon is based on three specimens collected from the margins of Arroyo Chasicó, Buenos Aires Province, (Argentina), which correspond to the Arroyo Chasicó Formation (late Miocene, Chasicoan SALMA). The new species is characterized by osteoderms with a very rough exposed surface showing high longitudinal and well developed crests (two lateral and one central) with deep and ample valleys among them. The new taxon is the only “relictual” xenarthran cingulate of the Santacrucian Age (late early Miocene) to be registered for the last time in the Chasicoan SALMA (late Miocene), and represents the youngest record of the family Peltephilidae.